PREVALENCE OF MALNUTRITION AMONG SCHOOL AGE CHILDREN INSABON GARI LOCAL GOVERNMENT AREA, KADUNA STATE - Olagunju, Abbas; Halimatu, Sadiya Abdullahi; Olumuyiwa, Adeyemi Owolabi (FUDMA Journal of Sciences, 2025)
The study assessed the prevalence of malnutrition among school-age children in Sabon Gari Local Government Area, Kaduna state, using a multi-stage cross-sectional study design. Two hundred and ninety-seven school-age children of both sexes were selected and standard anthropometric techniques were used as described by WHO. Socio-demographic analysis revealed that 86.2% of the children attend schools. Gender balance was observed, with 49.8% males and 50.2% females. The majority of the school- age children belong to the Hausa ethnic group (73.8%), followed by Fulani (12.4%), Yoruba (4.8%), and Igbo (4.8%) ethnic groups. Fathers of school-age children were primarily civil servants (42.5%), while their mothers were predominantly involvedtrading (46.6%). Anthropometric indicators of Weight-for-Age Z score (WAZ) indicated that 37.1% of the children had normal weight-for-age, 25.2% were moderately underweight (< -2 Z score) and 1.4% were severely underweight (<-3 Z score), Height-for-Age Z score (HAZ) showed that 30.0% had normal height-for-age, while 26.6% were moderately stunted (< -2 Z score) and 11.8% were severely stunted (< -3 Z score). BMI-for-Age Z score (BAZ) revealed that 37.0% had a normal body mass index for age, while 15.5% exhibited moderate thinness (< -2 Z score) and 10.4% were severely thin (< -3 Z score). Malnutrition continues to be a public health concern among school-age children, anthropometric measurements revealed differences in nutritional health, highlighting the importance of combating underweight, stunting and thinness. Thus, findings provided valuable insights for tailored strategies aimed at improving the nutritional outcomes of school-age children in Sabon Gari LGA, Kaduna State.